The Halloween indicator, "Sell in May and Go Away": Everywhere and all the time. (February 2021) - Zhang, Cherry Y.; Jacobsen, Ben
Highlights: We use all historical stock market data to verify the Halloween effect. The 6-month returns on average is 4% higher during November-April than May-October. Worldwide excess returns during summer are often significantly negative. . Our dataset allows for a new (upper bound) estimate for the equity premium of around 4%. Abstract: To answer the sceptics, we use all historical data (62962 observations) on all stock market indices worldwide to verify the robustness of the so-called Halloween Indicator or Sell in May effect. The effect seems remarkably robust with returns on average 4% higher during November-April period than during May-October. A new test for the effect offers some additional insights. Worldwide excess returns during summer seem negative (around −1%) and often significantly so suggesting a flat or negative risk return relation. Only for Mauritius do we find a significantly positive risk return relation during May-October. Our dataset also allows for a new (upper bound) estimate for the equity premium of around 4%.